THE CONCEPT, IMPORTANCE AND CHARACTERISTICS OF ELECTRONIC CURRENCY (TSUL LEGAL REPORT, 2026)
The article analyzes the legal nature of the electronic currency. It is of scientific research interest, since the main task of the state in the field of electronic payments is not only to create a legal climate, protect the participants in the settlement, increase transparency and legalization, but also create equal conditions for the development of electronic cash and virtual money. As well as, in the context of the global financial and economic crisis, the fall in public confidence in the banking system and state currencies, the ideas of creating new, alternative currency systems have become especially relevant. The most famous is an electronic currency protected by a cryptographic coding system, which is why it is called a crypto currency. A number of authors’ publications have already discussed the features of electronic currency. Within the framework of this article, the legal foundations of the issue under study will be touched upon. For the World Bank, ministries of finance and central banks of different countries, the problem of the existence of virtual, or cryptocurrencies, is relevant.